East Midlands knee pain multiple randomised controlled trial cohort study: cohort establishment and feasibility study protocol. Issue 9 (9th September 2020) - Hall, Michelle; Fuller, Amy; Nomikos, Polykarpos Angelos; Millar, Bonnie; Ogollah, Reuben; Valdes, Ana; Greenhaff, Paul; das Nair, Roshan; Doherty, Michael; Walsh, David A; Abhishek, A
Abstract : Introduction: Knee pain due to osteoarthritis (OA) is a common cause of disability. The UK National Institute for Health and Care Excellence OA guidelines recommend education, exercise and weight loss advice (if overweight) as core interventions before pharmacological adjuncts. However, implementation of these in primary care is often suboptimal. This study aims to develop a complex intervention with non-pharmacological and pharmacological components that can be delivered by nurses. The feasibility and acceptability of the intervention, and feasibility of undertaking a future cohort randomised controlled trial (RCT) will be explored. Methods and analysis: In phase 1, we will develop a training programme for nurses and evaluate the fidelity and acceptability of the non-pharmacological element of the intervention. Fidelity checklists completed by the nurse will be compared with video analysis of the treatment sessions. Patients and nurses will be interviewed to determine the acceptability of the intervention and explore challenges to intervention delivery. The non-pharmacological component will be modified based on the findings. In phase 2, we will assess the feasibility of conducting a cohort RCT comprising both the pharmacological and modified non-pharmacological components. We will compare three groups: group A will receive the non-pharmacological components delivered before pharmacological components; group B will receive pharmacological components followed by the non-pharmacological components; and group C (control arm) will continue to receive usual care. Study outcomes will be collected at three time points: baseline, 13 and 26 weeks after randomisation. Qualitative interviews will be conducted with a sample of participants from each of the two active intervention arms. Ethics and dissemination: This protocol was approved by the East Midlands-Derby Research Ethics Committee (18/EM/0288) and registered at ClinicalTrials.gov (protocol v4.0, 10/02/2020). The study will be reported in accordance with the Consolidated Standards of Reporting Trials guidance and standards. The results will be submitted for publication in peer-reviewed academic journals. Trial registration number: NCT03670706